Relationship Between Educational Institution, School Building, and School Food Factors and High School Students’ Satisfaction - Lozano Treviño, David Fernando (2026)
This study aims to examine the association between Educational Institution, School Building, and School Food factors and student satisfaction in a Mexican high school. The research employed a non-experimental, correlational design using data from the 2023 Institutional Quality Survey. The sample consisted of 3,979 students. Exploratory and Confirmatory Factor Analyses were applied, yielding three independent components (KMO = .959). To construct the dependent factor, Cronbach’s alpha was calculated, resulting in a reliability coefficient of .718. A Multiple Regression Analysis was conducted to assess the influence of the latent components on the dependent variable. The findings confirm the proposed hypotheses: the Educational Institution factor is the strongest predictor of student satisfaction, while School Food and School Building exert comparatively lower influence.